Interactions between C : N : P stoichiometry and soil macrofauna control dung decomposition of savanna herbivores. (21st January 2014) - Sitters, Judith; Maechler, Marc‐Jacques; Edwards, Peter J.; Suter, Werner; Olde Venterink, Harry; Kay, Adam
Summary Although dung of mammalian herbivores is an important pathway for nutrient return in savanna ecosystems, differences in dung decomposition rates among species have been little studied. We measured the rates of dung deposition and decomposition for various herbivores in a moist Tanzanian savanna and the related differences among species to nutrient concentrations and the activities of soil macrofauna (e.g. different mesh sizes of decomposition bags, or presence and absence of dung beetles). Dung C : N : P stoichiometry varied widely among species, which could in part be explained by differences in feeding strategy (browsers vs. grazers) and digestive physiology (ruminants vs. non‐ruminants). Rates of both decomposition and nutrient release were influenced by the C : N : P stoichiometry of dung, with lower relative losses of the least abundant nutrient in the dung. Surprisingly, soil macrofauna increased the relative losses of the least abundant nutrient, thereby stabilizing the ratio of N loss to P loss. Dung beetles increased rates of N and P release from wildebeest dung significantly and also increased N availability in the soil. We conclude that rates of nutrient return in dung depend not only on where herbivores deposit their dung, but also on its C : N : P stoichiometry, the activity of soil macrofauna and interactions between these factors. These factors may therefore influence the relative availabilities of N and P in the soil and hence the functioning of savanna ecosystems.